A Comparative Study of the Study of Mainstreaming Management Special Education According to Standards in School Under Nakohn Pathom Primary Education Services Area Office 2 - Rungmuang, Tinnakrittapat; Supabhato, Phrapalad Prapoj (Arts of Management Journal, 2020)
This research aimed to study the management of special education classes by school classes. School district primary education office 2. A sample was selected from 302 cases were drawn from school administrators and teachers. The statistical analysis was frequency, percentage, mean ( ), standard deviation (SD). Data was analyzed using t-test, ANOVA (one-way ANOVA) and pairwise comparison by way of LSD (Least significance difference). The findings were as follows: 1) The study of mainstreaming management special education according to standards in school under Nakohn Pathom primary education services area office 2 at a high level ( =3.54). When considering in each aspect, it was found that the student and teaching and learning activities High level ( = 3.83, 3.82) in terms of environment and tools Moderate level ( = 3.42, 3.08) 2) Position and work experience, it was found that the administrators and teachers had that position and work experience. There was a different educational administration according to the different standard of study.